Molecular characterization and detection of variants of Taenia multiceps in sheep in Turkey - Sonmez, Betul; Koroglu, Ergun; Simsek, Sami (Cambridge Univ Press, 2017)
Taenia multiceps is a cestode (family Taeniidae) that in its adult stage lives in the small intestine of dogs and other canids. The metacestode, known as Coenurus cerebralis, is usually found in the central nervous system including brain and spinal card in sheep and other ruminants. The presence of cysts typically leads to neurological symptoms that in the majority of cases result in the death of the animal. Coenurosis could cause high losses in sheep farms because the disease commonly affects young animals. A total of 20 C. cerebralis isolates collected from naturally infected sheep in Mardin province of Turkey were characterized through the polymerase chain reaction and sequencing of a fragment of cytochrome c oxidase subunit 1 (CO1) gene. The results showed that the CO1 gene sequences were highly conserved in C. cerebralis isolates. Phylogenetic analysis based on partial CO1 gene sequences revealed that C. cerebralis isolates were composed of three different variants.
Keywords: Taenia multiceps; Coenurus cerebralis; sheep; variant; CO1; PCR; Turkey